Moderate Hepatic Impairment Does Not Affect Doravirine Pharmacokinetics. (27th December 2016) - Khalilieh, Sauzanne; Yee, Ka Lai; Liu, Rachael; Fan, Li; Sanchez, Rosa I.; Auger, Patrice; Triantafyllou, Ilias; Stypinski, Daria; Lasseter, Kenneth C.; Marbury, Thomas; Iwamoto, Marian
Abstract: Doravirine is a novel, potent, nonnucleoside reverse‐transcriptase inhibitor currently in development for HIV‐1 infection treatment. As a substrate for CYP3A‐mediated metabolism, doravirine could potentially be affected by liver‐function changes. As a portion of the HIV‐1‐infected population has varying degrees of liver impairment, we investigated the effect of moderate hepatic impairment on the pharmacokinetic profile and tolerability of single‐dose doravirine 100 mg in otherwise healthy subjects. A total of 16 subjects aged 44–64 years took part in the open‐label, single‐dose trial: 8 with moderate hepatic impairment (Child‐Pugh score, 7–9; 6 men, 2 women) and 8 healthy individuals (mean age and height matched with the impairment group; 6 men, 2 women). Subjects with hepatic impairment were required to have chronic, stable hepatic impairment with features of cirrhosis of any etiology. Blood sampling revealed that doravirine exposure was similar in both groups. The observed geometric least‐squares mean ratio (90% confidence interval; moderately impaired/healthy subjects) was 0.99 (0.72–1.35) for AUC0–∞, 0.93 (0.74–1.18) for AUC0–24 h, 0.90 (0.66–1.24) for Cmax, and 0.99 (0.74–1.33) for C24 h . Geometric mean apparent terminal t½ was ∼18 hours for both groups, whereas median Tmax was 2 hours (range, 1–6 hours) and 2.5 hours (range, 1–3 hours) for impaired and healthy individuals, respectively. In addition, doravirine was generally well tolerated. The results demonstrate that moderate hepatic impairment does not have a clinically meaningful effect on doravirine pharmacokinetics. Therefore, dose adjustment should not be necessary in patients with both HIV‐1 and moderate hepatic impairment.